Effect of prenatal cocaine on early postnatal thermoregulation and ultrasonic vocalization production - McMurray, Matthew S.; Zeskind, Philip S.; Meiners, Stephanie M.; Garber, Kristin A.; Tien, Hsiao; Johns, Josephine M. (Frontiers in Psychology, 2013)
Prenatal cocaine exposure can alter the postnatal care received by rat pups. Such effects could be caused in part by alterations in pup-produced stimuli that elicit early postnatal maternal care. Pup ultrasonic vocalizations are thought to be a particularly salient stimulus, and when paired with other cues, may elicit maternal attention. Cocaine is known to acutely alter thermoregulatory and cardiac function, thus prenatal cocaine may affect vocalizations through altering these functions. The data presented here determine the impact of full term prenatal cocaine exposure , saline exposure, or no exposure on thermogenic capacity, cardiac function, and the resulting ultrasonic vocalizations across the early postnatal period (days 1-5). Results indicated that while sharing many similar characteristics with saline-exposed and untreated animals, prenatal cocaine exposure was associated with specific alterations in vocalization characteristics on postnatal day 1 (PND 1), including call amplitude. Furthermore, numerous spectral parameters of their vocalizations were found altered on PND 3, including rate, call duration, and frequency, while no alterations were found on PND 5. Additionally, cocaine-exposed pups also showed a reduced thermoregulatory capacity compared to saline animals and reduced cardiac mass compared to untreated animals on PND 5. Together, these findings indicate that prenatal cocaine may be altering the elicitation of maternal care through its impact on vocalizations and thermoregulation, and suggests a potential mechanism for these effects through cocaine’s impact on developing stress systems.